A Cholesterol‐Dependent Endocytic Mechanism Generates Midbody Tubules During Cytokinesis. (23rd September 2015) - Kettle, Emma; Page, Scott L.; Morgan, Garry P.; Malladi, Chandra S.; Wong, Chin L.; Boadle, Ross A.; Marsh, Brad J.; Robinson, Phillip J.; Chircop, Megan
<x xml:space="preserve">Abstract</x> Electron tomography reveals that many vesicles within the intracellular bridge (ICB) of a cytokinetic cell are not independent but connected, forming a newly described ICB vesicular structure – narrow midbody tubules that are often branched. Endocytosis occurs at the rim of the ICB via a dynamin‐independent cholesterol‐dependent mechanism and contributes to the extensive accumulation of membrane‐bound structures in the ICB. Thus, ICB vesicles generated via endocytosis are not solely dependent on the recycling endocytic pathway but also involve locally occurring endocytosis. Red, plasma membrane; green, microtubules; dark blue, small vesicles; yellow, tubules within the ICB; white, small vesicles and tubules within peri‐ICB; orange, multivesicular bodies; light blue, membrane which is unclear if it is continuous with outer plasma membrane.<boxed-text content-type="graphic" id="tra12328-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>